Adventitious facts in civil litigation In Iranian and French law - Kheyrollah Hormozi; Masoomeh Keshtkari (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2022)
The subject matter of the claim form is determined by the claims of the parties in the claim form and the defense bills, so the scope of the court in the proceedings will be determined. However, among the elements raised by the parties, there are facts that neither of them has explicitly cited in order to benefit from its legal effects. Moreover, the judge was able to legitimately inform them because it arises from the more general claims of the parties or the documents presented in the case file. These are called Adventitious facts. The question is; “Is it possible for the court to deal with these facts?” Examining the various dimensions of the case shows that accepting the judge's ability to identify these facts in order to benefit from them is accompanied by ambiguities. While the judge's ability to identify and benefit from Adventitious facts is not in dispute in France, this paper attempts to address these ambiguities by focusing on French law. It seems that in Iranian legal system- despite of the lack of a comprehensive legal doctrine in this area- traces of Adventitious facts can be seen in the rulings issued by the courts.